2022
DOI: 10.3390/fermentation8060264
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Component Adjustment of Distilled Dried Grain with Solubles via Aspergillus niger and Its Change about Dynamic Physiological Metabolism

Abstract: The low fiber digestibility and unbalanced amino acids restricted the use of DDGS in swine diets. Key nutrition components dynamic monitoring and key regulatory pathways analysis were performed to find the rules of nutrition changes for DDGS fermented by Aspergillus niger. Cellulose and hemicellulose were reduced to 15.3% and 15.2%. 1,4-D-Xylobiose was decreased from 16.8 μg/mL to 0.2 μg/mL. Lys, Arg, and Thr were increased to 3.00%, 2.89%, and 4.40%, and met the requirements of pigs. The whole fermentation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the present study, SSF of DDGS with A. ibericus increased nitrogen content by about 16%, and soluble protein content was 18 times higher than with the unfermented DDGS. Similarly, SSF of DDGS with A. niger increased protein content circa 22%, from 9.5% to 11% wet weight [66]. SSF with Pleurotus sapidus also increased rice bran protein content from 7.4% to 12.8% [67].…”
Section: Solid-state Fermentationmentioning
confidence: 84%
“…In the present study, SSF of DDGS with A. ibericus increased nitrogen content by about 16%, and soluble protein content was 18 times higher than with the unfermented DDGS. Similarly, SSF of DDGS with A. niger increased protein content circa 22%, from 9.5% to 11% wet weight [66]. SSF with Pleurotus sapidus also increased rice bran protein content from 7.4% to 12.8% [67].…”
Section: Solid-state Fermentationmentioning
confidence: 84%
“…The DW of mycelium continued to increase to 0.80 ± 0.04 and 0.88 ± 0.02 g/100 mL within 96 h in OP and PDB media, respectively. However, it decreased to 0.76 ± 0.01 g/100 mL in PDB, while that in OP tended to be flat between 96 and 120 h. One possible explanation for this is that it takes longer for A. niger to reach the recession stage in OP because of the decomposition of OP cellulose (Fan et al ., 2022). The OP powder had the carbohydrate consisted of about 20% lignin, 69% cellulose and 9% hemicellulose for strain consumption, which could not be used up by strain without first being enzymatically hydrolysed to monosaccharides (Ayala et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Zhang also found that the main metabolites involved in the TCA cycle stimulate cellulose degradation by bacteria belonging to the phylum Bacteroidetes (Zheng et al, 2021). In addition, malic acid can also be produced by glycolaldehyde and mesaconic acid because α-ketoglutarate is a precursor for the synthesis of lysine, and α-ketoglutarate is not only consumed in the TCA cycle, but it is also consumed by the synthesis of lysine, which is also the reason why the content of oxoglutaric acid does not change significantly (Fan et al, 2022). Glucose was not detected in either the stone cell group or the supernatant group, probably because glucose was converted to pyruvate and then entered the TCA cycle, which also provided more energy for microbial growth.…”
Section: Discussionmentioning
confidence: 99%